Inhibition of cobalamin‐dependent methionine synthase by substituted benzo‐fused heterocycles - Banks, Elizabeth C.; Doughty, Stephen W.; Toms, Steven M.; Wheelhouse, Richard T.; Nicolaou, Anna (The FEBS journal, 2007)
The cobalamin–dependent cytosolic enzyme, methionine synthase (EC.2.1.1.13), catalyzes the remethylation of homocysteine to methionine using 5‐methyltetrahydrofolate as the methyl donor. The products of this remethylation – methionine and tetrahydrofolate – participate in the active methionine and folate pathways. Impaired methionine synthase activity has been implicated in the pathogenesis of anaemias, cancer and neurological disorders. Although the need for potent and specific inhibitors of methionine synthase has been recognized, there is a lack of such agents. In this study, we designed, synthesized and evaluated the inhibitory activity of a series of substituted benzimidazoles and small benzothiadiazoles. Kinetic analysis revealed that the benzimidazoles act as competitive inhibitors of the rat liver methionine synthase, whilst the most active benzothiadiazole (IC50 = 80 µm) exhibited characteristics of uncompetitive inhibition. A model of the methyltetrahydrofolate‐binding site of the rat liver methionine synthase was constructed; docking experiments were designed to elucidate, in greater detail, the binding mode and reveal structural requirements for the design of inhibitors of methionine synthase. Our results indicate that the potency of the tested compounds is related to a planar region of the inhibitor that can be positioned in the centre of the active site, the presence of a nitro functional group and two or three probable hydrogen‐bonding interactions.